Trends in contraceptive use, unmet need and associated factors of modern contraceptive use among urban adolescents and young women in Guinea - Sidikiba Sidibé; Alexandre Delamou; Bienvenu Salim Camara; Nafissatou Dioubaté; Hawa Manet; Alison M. El Ayadi; Lenka Benova; Seni Kouanda (BMC, 2020)
Abstract Background In Guinea, high fertility among adolescents and young women in urban areas remains a public health concern. This study describes trends in contraceptive use, unmet need, and factors associated with the use of modern family planning (FP) methods among urban adolescents and young women in Guinea. Methods We used four Guinea Demographic and Health Surveys (DHS) conducted in 1999, 2005, 2012, and 2018. Among urban adolescents and young women (15-24 years), we examined trends over time in three key indicators: 1. Modern Contraceptive use, 2. Unmet need for FP and 3. Modern contraceptive use among those in need of FP (demand satisfied). We used multivariable logistic regression to examine association between socio-demographic factors and modern FP use on the most recent DHS dataset (2018). Results We found statistically significant changes over the time period examined with an increase in modern contraceptive use (8.4% in 1999, 12.8% in 2018, p < 0.01) and demand satisfied (29.0% in 1999, 54.1% in 2018, p < 0.001), and a decrease in unmet need for FP (15.8% in 1999, 8.6% in 2018, p < 0.001). Factors significantly associated with modern FP use were; young women aged 20-24 years (AOR 2.8, 95% CI: 1.9-4.1), living in urban areas of Faranah (AOR: 2.6, 95% CI: 1.1-6.5) and Kankan (AOR: 3.6, 95% CI: 1.7-7.8), living in households in the middle (AOR: 7.7, 95% CI: 1.4-42.2) and richer wealth quintiles (AOR: 6.3, 95% CI: 1.0-38.1). Ever-married women (AOR: 0.5, 95% CI: 0.3-0.9) were less likely to use modern FP methods than never married as were those from the Peulh (0.3, 95% CI: 0.2-0.4) and Malinke (0.5, 95% CI: 0.3-0.8) ethnic groups compared to Soussou ethnic group. Conclusion Despite some progress, efforts are still needed to improve FP method use among urban adolescent and young women. Age, administrative region, wealth index, marital status, and ethnic group are significantly associated with modern FP use. Future policies and interventions should place emphasis on improving adolescents' reproductive health knowledge, increasing FP availability and strengthening provision. Efforts should target adolescents aged 15-19 years in particular, and address disparities between administrative regions and ethnic groups, and health-related inequalities.